MATERNAL RISK FACTORS OF LOW BIRTH WEIGHT (LBW): SYSTEMATIC REVIEW - Jianti Fina Lestari; Risa Etika; Pudji Lestari (Indonesian Midwifery and Health Sciences Journal, 2020)
Abstract Background: Low Birth Weight Babies (LBW) accounts for 60 - 80% of all neonatal deaths in the world. Not the only major predictor of mortality and morbidity in neonates, individuals with a history of LBW have a greater risk of experiencing various diseases such as hypertension, heart disease, and diabetes later in life. This systematic review study aims to identify maternal risk factors that contributing to LBW Method: Articles published between 2015 - 2020 in the Science Direct, Scopus and Cochrane library databases are systematically reviewed. Eleven articles that met the inclusion and exclusion criteria were included as samples for further review. Results regarding maternal risk factors for LBW events are synthesized systematically .Results: From the search results, there were 818 articles, after the screening process, the final results were 11 articles. Risk factors that are significantly related to LBW incidence in the article, are grouped in the subtheme, include: maternal age (<20 years, and each increase in age), parity (primipara and grandemultipara), low maternal upper arm circumference, hemoglobin levels less than 11 gr / dl, gestational age below 37 weeks, and complications during pregnancy. Conclusion: maternal age, parity, arm circumference, hemoglobin level, gestational age, and complications during pregnancy were significaly found to be maternal risk factors for LBW.